2022
DOI: 10.1155/2022/4336822
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time Biometric Encryption Scheme Based on Fuzzy Logic for IoT

Abstract: When milliards of smart devices are connected to the Internet using the Internet of Things (IoT), robust security methods are required to deliver current information to the objects. Using IoT, the user can be accessed via smart device applications at any time and any place, which challenges IoT security and privacy. From security point of view, users and smart devices should have secure communication channel and digital ID. Authentication is the first step towards any security action. Biometric-based authentic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The task allocation model improves the adaptation and efficiency of mobile crowdsourcing systems. The location privacy-preserving scheme CKD via differential privacy-preserving and k-anonymity was proposed by Chi et al 18 While the trade-off between service quality and privacy security is successfully resolved, this approach needs to address the social relationship between workers in terms of privacy.…”
Section: B To Extract Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The task allocation model improves the adaptation and efficiency of mobile crowdsourcing systems. The location privacy-preserving scheme CKD via differential privacy-preserving and k-anonymity was proposed by Chi et al 18 While the trade-off between service quality and privacy security is successfully resolved, this approach needs to address the social relationship between workers in terms of privacy.…”
Section: B To Extract Featuresmentioning
confidence: 99%
“…The task allocation model improves the adaptation and efficiency of mobile crowdsourcing systems. The location privacy‐preserving scheme CKD via differential privacy‐preserving and k‐anonymity was proposed by Chi et al 18 While the trade‐off between service quality and privacy security is successfully resolved, this approach needs to address the social relationship between workers in terms of privacy. A multi‐dimensional quality‐driven service recommendation with a privacy‐preservation model was proposed by Zhong et al 19 The experimental result demonstrated better feasibility in terms of multiple quality of service dimensions with privacy‐preserving edge service recommendations, but it was unsuitable for real‐world experiments.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…2 Designing security system has given increasing consideration to person verification based on biometric characteristics. 3 The performance requirements in realworld systems cannot be satisfied by single biometric characteristic. The majority of biometric systems have a high false rejection rate (FFR) and are neither user-friendly nor confident with users.…”
mentioning
confidence: 99%